Chimen an nou, une carte contributive pour se rapprocher du territoire - Bertilla Baudinière; Jeanne Lacour (Projets de Paysage)
Chimen an nou is intended to develop the practice of walking and cycling on a daily basis in the area of the conurbation of Cap Excellence in Guadeloupe. A contributory digital tool was combined with fieldwork and public events to disseminate sensory knowledge of the territory and invite people to experiment with new ways of getting around. This article presents a series of interactions between individual and collective practices, sensory experiences and digital tools, and a dialogue between urban architects, the GIS expert, residents and public authorities. We first look at how digital technology accompanied the project throughout the process and enabled it to evolve, we then look at how the use of open source technologies helped residents appropriate the project, and finally we study the link between sharing fragments of landscape experience on a digital map and disseminating practices in the field.